Why Turn to Hegel Today? An Introduction - Battistoni, Giulia (ETHICS IN PROGRESS, 2024)
This brief introduction sets the stage for the central aim of this issue of Ethics in Progress devoted to Hegel: to underscore the enduring relevance of his thought, in particular his Philosophy of Nature and his Realphilosophie, in addressing contemporary challenges. While Hegel may appear to some as an abstract thinker, seemingly surpassed by the demands of our era, the core elements of his philosophy – particularly the dialectical method, his reflections on the complex relationship between Natur (nature) and Geist (spirit), and key concepts such as Anerkennung (recognition) and Wille (will) – continue to provide a vital conceptual framework for addressing pressing issues of our time. These include the environmental crisis and the evolving dynamics between humanity, nature, and emerging technologies like artificial intelligence. Consequently, this issue strives to approach Hegel through the lens of our contemporary experience, not to distort or “denaturalize” his thought, nor to fall into the trap of anachronism, but to breathe new life into the concept. By doing so, it invites the reader to listen anew to what Hegel’s philosophy might still teach us today.